A phylogenetic and taxonomic study on Steccherinum (Polyporales, Basidiomycota): Focusing on three new Steccherinum species from southern China - Dong, Jun-Hong; Zhang, Xun-Chi; Chen, Jia-Jia; Zhu, Zhong-Long; Zhao, Chang-Lin (Frontiers in Cellular and Infection Microbiology, 2023)
The wood-inhabiting fungi play an integral role in wood degradation and the cycle of matter in the ecological system. They are considered as the “key player” in wood decomposition, because of their ability to produce all kinds of enzymes that break down woody lignin, cellulose and hemicellulose. In the present study, three new wood-inhabiting fungal species, Steccherinum fissurutum, S. punctatum and S. subtropicum spp. nov., collected from southern China, are proposed based on a combination of morphological features and molecular evidence. Steccherinum fissurutum is characterized by the resupinate, subceraceous basidiomata with cracked hymenophore, a monomitic hyphal system with clamped generative hyphae and cylindrical basidiospores; S. punctatum is characterized by the annual, punctate basidiomata with leathery hymenophore, cylindrical, strongly encrusted cystidia and ellipsoid basidiospores (3.6–4.5 ×2.6–3.4 µm); S. subtropicum is characterized by its effuse-reflexed basidiomata, a odontioid hymenophore with pink to lilac hymenial surface and ellipsoid basidiospores measuring as (2.8–3.4 × 2.0–2.7 µm). Sequences of ITS and nLSU rRNA markers of the studied samples were generated, and phylogenetic analyses were performed with maximum likelihood, maximum parsimony, and Bayesian inference methods. The ITS+nLSU analysis of the family Steccherinaceae indicated that the three new species clustered into the genus Steccherinum. Based on further analysis of ITS+nLSU dataset, the phylogenetic analysis confirmed that S. subtropicum was sister to S. enuispinum; S. fissurutum formed a monophyletic lineage; S. punctatum grouped with a clade comprised S. straminellum and S. ciliolatum.